Van der Woude Syndrome Associated with Hypodontia: A Rare Clinical Entity - Romesh Soni; Rajul Vivek; Adit Srivastava; Ankita Singh; Shalabh Srivastava; T. P. Chaturvedi (Case Reports in Dentistry)
Van der Woude syndrome (VWS) is usually underreported and frequently not diagnosed. The phenomenon that cleft lip and palate are regularly combined in the same pedigree makes it unique. A meticulous examination of a patient with lip pits may reveal a hidden form of a cleft, for example, submucous. This paper presents a case of VWS in a ten-year-old boy with characteristic orofacial features. Special emphasis has also been given on the need for appropriate genetic counseling.